Penganekaragaman Formula Makanan Dengan Pemanfaatan Dadih Susu Kerbau Untuk PMT Fungsional Anak Balita - M Husni Thamrin; Ismanilda .; Marni Handayani . (Jurnal Sehat Mandiri, 2017)
Based on Data of Basic Research 2010, the prevalence of malnutrition and undenutrition in West Sumatera is 20,2%, While the prevalence of undernutrition for Padang City is 15,1%. Curd is one of functional foods to be there in West Sumatera which contains the adequate nutrition consisting of carbohydrate contents 3,34%, protein 5,93%, fat 5,42%, and level of water 84,35%. This aim for research is producted food formula to children under 5 years old with diversification of food raw in making functional formula from Curd of buffalo milk. This research is experiment by the diversivication of raw foods from Curd of buffalo milk with mixture of wheat flour, flour of red sweet potato, soya flour and sugar flour. This design of research is using Completely Randomized Design (CRD) consisting of 6 treatments and 2 repetitions. Observation is done for organoleptic test in cake to be made. Result of observation is analyzed by Analysis of Variance (Anova). And continued by Duncan Test/DNMRT at the level 5%.Color and aroma cake curd most preferred by the panelists was the addition of 140 g of buffalo milk curd while adding flavor and texture of the curd 120 gr addition of curd 160 gr.The best treatment in curd cake which is the most preferred by the panelist is in the F2 Treatment with the addition of curd of 120 gr buffalo milk.